Kondisi Fisik Atlet Judo Jawa Barat Pada Saat Pandemic COVID-19: Tinjauan Tahap Persiapan Umum - Purnamasari, Ira; Listiandi, Arfin Deri; Novian, Geraldi; Hidayat, Budi (Journal of Sport Science and Education, 2022)
The COVID-19 pandemic that has hit the whole world has disrupted various important things, including the match agenda, including the holding of PON (National Sports Week) which had to be postponed. The exercise program that has been carried out by athletes has also been disrupted, especially physical exercise that must be done at home. The purpose of this study was to determine the physical condition of the results of training carried out by West Java Judo athletes during the general preparation period, which was also constrained by the existence of a home exercise program at the beginning of the COVID-19 pandemic. The method used in this study is a descriptive method using research instruments 1) aerobic capacity: balke test; (2) an-aerobic capacity: 300 meters-run test; (3) strength endurance: 1-minute push up test and 1-minute sit-up test; (4) core stabilization: core stabilization test. The sample in this study were 18 athletes of West Java Judo PON Pelatda PON XX athletes. The t-test was used as a data analysis technique for this research. The results showed that there was a significant effect of the exercise carried out on the physical condition of the athlete at the general preparation stage. An increase in every component of the athlete's physical condition also occurred, although some of them experienced no change or even a decrease. This is due to the constraints of the training program that must be faced during the time of training at home independently, so athletes are constrained by limited facilities, unlike the facilities provided in the centralized training center. Motivation to practice also affects the factor of practicing during the training period at home during the COVID-19 pandemic.